Plant clinic in Nepal: An overview - Adhikari, Debraj; Pandit, Vinod; Bhatta, Madav; Sharma, Dilli Ram; Baral, Sabitri (Acta Agraria Debreceniensis, 2024)
Plant clinics play an important role in supporting farmers in growing healthy crops and achieving higher productivity in Nepal. The development and operation of plant clinics in Nepal are assessed in this study through a comprehensive analysis of the institution via literature review and interaction with key stakeholders. The plant clinic approach of the agriculture extension system started in Nepal in 2008, followed up with engagement with CABI and the Government of Nepal. Enhancement of farmers' knowledge and skill, encouraging sustainable farming methods, and ultimately increasing crop yields are the impact of plant clinics. However, there are some challenges faced during the implementation of plant clinics in the existing agricultural extension systems. In Nepal, the plant clinics are primarily operated by agricultural technicians with expertise in plant protection, as well as IPM farmer facilitators and community business facilitators after attending an intensive plant doctor's training. Plant clinics have been integrated into the agricultural extension system by agro-advisory service provider of the government of Nepal. Despite institutionalisation, policy support needs to be strengthened to ensure the sustainability of the different components of the (e.g., data management, validation, monitoring, localised content, etc.) plant clinic in Nepal.